Epidemiological survey of Trichinella infection in domestic, synanthropic and sylvatic animals from Argentina - Krivokapich, Silvio (2006)
Fil: Krivokapich, S J. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.